On procedural discoursivation - or how local utterances are turned into binding facts = Prozessuale Diskursivierung - oder wie lokale Äußerungen in bindende Tatsachen verwandelt werden - Scheffer, Thomas (2007)
The article deals with a fundamental mechanism here referred to as 'discoursivation' meaning the transformation of local utterances into available and binding discursive facts. Discoursivation, it is claimed, lies at the heart of (legal) discourse formation since it provides the basic material for all the operations to follow such as defining, assessing, and deciding. The basic mechanism is explored in light of two models: Luhmann's "procedural past" and Foucault's "field of presence". Do these models grasp the mechanism of discoursivation? Three criminal cases provide the empirical reference for the conceptual endeavour. In each of these cases, the analysis traces the suspect's early defence and the multiple reappearances and references to it in the procedural course. On these grounds, the article distinguishes three modes of discoursivation. Utterances are turned into discursive facts by ways of staging, reiteration, and mobilisation. By using only one of these modes, an analysis